Творення нових прикметників в українській мові новітнього періоду(транспозиційні словотвірні типи) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article gives a broad outline of traditional and non-traditional approaches to defining the term «derivation», presents typology of derivational processes and highlights peculiarities of the nominative and communicative types of derivation.